2007
DOI: 10.1149/1.2436611
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Proton-Conducting Properties of Nafion–1,2,4-Triazole and Nafion–Benzimidazole Membranes for Polymer Electrolyte Fuel Cells

Abstract: Recently, fuel cells have gathered a lot of interest due to their potential as future sources of clean energy. Polymer electrolyte fuel cells ͑PEFCs͒ require high operating temperatures ͑100-200°C͒ for high conversion efficiency. Anhydrous proton-conducting polymers employing Nafion-1,2,4-triazole-and Nafion-benzimidazole-blend membranes were studied for use in PEFCs above 100°C. The solvents 1,2,4-triazole and benzimidazole are thermally stable, organic reagents with low volatility and are used to replace wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 38 publications
(38 reference statements)
0
61
0
Order By: Relevance
“…Imidazole was also used in many other composite membranes, which show great potential in PEMFCs [35][36][37], especially for the low humidity condition at high temperature. Triazole and its derivatives, which contain one more nitrogen than imidazole [34,[38][39][40][41], have also been found to show the potential to replace water in high temperature PEMFCs, as shown in Figure 3b. Ghassemi et al [34,38] did extensive work on triazole-containing composite membranes and showed that the triazole derivatives are viable proton transport facilitators.…”
Section: Nafion-based Acid-base Membranesmentioning
confidence: 99%
“…Imidazole was also used in many other composite membranes, which show great potential in PEMFCs [35][36][37], especially for the low humidity condition at high temperature. Triazole and its derivatives, which contain one more nitrogen than imidazole [34,[38][39][40][41], have also been found to show the potential to replace water in high temperature PEMFCs, as shown in Figure 3b. Ghassemi et al [34,38] did extensive work on triazole-containing composite membranes and showed that the triazole derivatives are viable proton transport facilitators.…”
Section: Nafion-based Acid-base Membranesmentioning
confidence: 99%
“…1H-1,2,4-Triazole was used as solid state proton solvent in replacement of water in different polymer matrices such as sulfonated polysulfone and hybrid inorganic-organic polymer network [9], Nafion [32], poly(vinyl phosphonic acid) and poly(2-acrylamido-2-methyl-1-propane sulfonic acid) [33]. To date, no literature is available about the crystal morphology of a heterocycle in sulfonated polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] In some studies, amphoteric liquid molecules such as phosphoric acid, [16][17][18] imidazole, [19] benzimidazole, [20] and triazole [21] have been added to polymeric matrices to obtain high proton conductivities at temperatures above 100 8C. However, leaching of the mobile (e.g., liquid) molecules by water remains a severe problem when used in fuel cells.…”
Section: Introductionmentioning
confidence: 99%